Gian Paolo Tozzoli, diplomatico e scrittore - Baldocci, Pasquale (Rivista di studi politici internazionali, 2010)
Gian Paolo Tozzoli ranks among the most relevant diplomat-writers of the Italian career. Born in Naples in 1926, he obtained a degree in Literature at the University of Bari and one in Law at Naples. He won the competition for the diplomatic service in 1954 and continued his activity as a journalist, later becoming an essayist, a poet, a novelist. He was posted in Belgrade, Basle, Geneva and New York as secretary and counsellor; successively in Tirana, Prague and Malta as ambassador. After three volumes of poetry: One hundred poems for a life, Malastrana and Suddenly, the world, he published an essay on Switzerland and the Swiss translated in German with the title Fünf Millionen Gerechte, The prophetic temptation on political prevision, and Albania, the last border of Stalinism. Switching to fiction, Tozzoli wrote two novels: Prince Dimitri and Apotheosis of an idiot, as well as various tales. His life and works confirm how diplomacy and literature can sometimes merge. Gian Paolo Tozzoli occupe une place de premier plan parmi les diplomates écrivains de la carrière italienne. Né à Naples en 1926, il s’est licencié en lettres à l’Université de Bari et en droit à Naples. Entré dans la carrière diplomatique en 1954, il a poursuivi son activité de journaliste, puis d’écrivain, de romancier et de poète tout au long de sa carrière, de Belgrade à Bàle, puis à Genève et à New York. Ambassadeur en Albanie, à Prague et à Malte, il fut président de l’Ispri (Institut pour les Études de Prévision et les Relations Internationales). Ses ouvrages principaux sont: La Suisse vue par un étranger, La tentation prophétique; trois volumes de vers: Cent poésies pour une vie, Malastrana et À l’improviste, le monde; deux romans: Le Prince Dimitri et Apothéose d’un imbécile, ainsi que de nombreuses nouvelles. Le lien unissant la diplomatie et la littérature est très évident dans son oeuvre, dans la tradition de Saint-John Perse, d’Andrié et de Seferis